A treatise on the outwardly nature of consciousness - Amin, Ramy (AUC Knowledge Fountain, 2020)
In this thesis we propose a sketch towards an outwardly understanding of the nature of consciousness. We begin by arguing that all thought involves phenomenal character, then establish that all phenomenal character involves phenomenal concepts, which allows us to conclude that all thought involves phenomenal concepts. Finally, we survey the philosophical theoretical space to ground our thesis within established theories of consciousness, perception, and epistemology.